The Effect of Job Satisfaction on Organizational Commitment Moderated by External Locus of Control - Wijaya, Lalu Hendra; Basit, Abdul (Sumber Belajar Sejahtera, 2024)
This study aims to find out the positive effect of job satisfaction on organizational commitment on outsourcing employees of commercial banks and to find out external locus of control in strengthening job satisfaction on organizational commitment on outsourcing employees of commercial banks. This type of data uses primary data. The data obtained directly from respondents who are the object of research, consisting of employees of commercial bank outsourcing in NTB province. The sample are 186 respondents from 23 commercial banks in NTB province. The results of this study show that job satisfaction is positively correlated with organizational commitment variables. A positive correlation means that the more outsourcing employees are satisfied with the job, the more committed they will be to the company where they work.